VIMENTIN EXPRESSION IN HUMAN CELL LINES OF EPITHELIAL TUMORS - T. A. Bogush; S. A. Kaliuzhny; M. R. Chetyrkina; M. A. Yastrebova; A. M. Scherbakov; I. A. Mamichev; А. А. Kamensky (Успехи молекулярной онкологии)
Background. Cell cultures used as a models in studies of epithelial tumors, are obtained not only from solid tumors, but also from extracellular fluids. It is known that dissemination of ovarian cancer in the peritoneum and further growth of tumor cells in ascetic liquid is accompanied with the activation of epithelial-mesenchymal transition, and, therefore, cell cultures derived from extracellular fluids can have a distinct molecular phenotype from primary tumors.Objective: evaluation the “persistence” of epithelial phenotype in breast and ovarian cancer cell cultures.Materials and methods. The cells obtained from pleural fluid (MCF-7, T-47D), colostrum (HBL-100), solid tumors (BT-474, HCC1937) of patients with breast cancer and ascitic fluid (SCOV- 3) of patients with ovarian cancer. The expression of cytokeratins and vimentin was evaluated using a quantitative immunofluorescence method associated with flow cytometry.Results. Vimentin expression in cells derived from extracellular fluids was not changed (line HBL-100), slightly decreased (SCOV-3 cells), or even was lost (MCF-7 and T-47D cells). HCC1937 cells obtained from solid tumor with expected low expression of vimentin acquired a molecular phenotype with a high expression of this mesenchymal marker. In breast cancer cells BT-474 derived from solid tumor a “persistence” of epithelial phenotype was discovered.Conclusion. Quantitative assessment of the de novo expression of mesenchymal protein vimentin showed that the tumor phenotype within the organizm is not always realized in cells adapted to growth in culture, and is not always «strictly» epithelial, and this evidence must be considered with different kinds of molecular studies of epithelial cells in vitro.